The crucial role of mitochondrial/chloroplast-related genes in viral genome replication and host defense: integrative systems biology analysis in plant-virus interaction - Shahriari, Amir Ghaffar; Tahmasebi, Aminallah; Ghodoum Parizipour, Mohamad Hamed; Soltani, Zahra; Tahmasebi, Ahmad; Shahid, Muhammad Shafiq (Frontiers in Microbiology, 2025)
Plant viruses participate as biotrophic parasites in complex interactions with their hosts, resulting in the regulation of a diverse range of chloroplast/mitochondria-related genes that are essential for mediating immune responses. In this study, integrative systems biology approaches were applied to identify chloroplast/mitochondrial genes during viral infections caused by a wide number of viruses in Arabidopsis thaliana, tobacco (Nicotiana tabacum L.), and rice (Oryza sativa L.). These findings indicated that 1.5% of the DEGs were common between Arabidopsis/tobacco and Arabidopsis/rice, whereas 0.1% of the DEGs were shared among all species. Approximately 90% of common DEGs are uniquely associated with chloroplasts and mitochondria in the host defense against viral infection and replication. The functions of WRKY, NAC, and MYB transcription factors in imparting resistance to viral infections can be established. Promoter analysis revealed that AP2/EREBP, DOF, and C2H2 zinc finger factors included the most frequent binding sites and played a more important role in plant-viral interactions. Comparative analysis revealed several miRNAs with defensive functions including miRNA156, miRNA160, and miRNA169. The PPI network revealed several key hub genes mostly related to chloroplasts/mitochondria, including ZAT6, CML37, CHLI, DREB, F27B13.20, and ASP2 with upregulation, also PLGG1, PSBY, APO2, POR, ERF, and CSP with downregulation. Moreover, novel hub genes with unknown functions, such as AT2G41640 and AT3G57380 have been identified. This study represents the first preliminary systems biology approach to elucidate the roles of chloroplast/mitochondria-related genes in Arabidopsis, tobacco, and rice against viral challenges by introducing valuable candidate genes for enhanced genetic engineering programs to develop virus-resistant crop varieties.